(untitled) (American Journal of Islam and Society, 1993)
This study is an examination of the tole of ethical imperatives and const&ts in the realm of international relations from the perspective of classical and modern Islamic theory. The study focuses upon three interrelated questions: (1) To what extent is an amoral conception of intemational politics possible within an Islamic framework? (2) To what extent is classical and/or modem Islamic theory compatible with the contemporary intemational system based upon the sovereign, independent nationstate? (3) What are the ramifications of Muslim accommodations with the theory of the sovereign nation-state in the aEas of just war, nuclear deterrence, and distributive justice? The historical development of Islamic thought and contemporary Muslim perspectives will be compared with the historical development of Western theories and contemporary Western perspectives on the tole of ethics in international relations. The purpose of this thesis is both to evaluate critically classical and contemporary Islamic perspectives on intemational relations and to develop systematically an Islamic ethical framework for issues still largely neglected by modem Muslim theorists: just war, the morality of nuclear detemce, and distributive justice. Theoretical Argument Is ethical theory applicable in the realm of international relations? If so, what role does or should it play in the conduct of foreign policy? The late international relations theorist Hedley Bull suggests h e philosophical strands in Western conceptions of intemational relations.’ Each is to some extent both descriptive as well as prescriptive. Each provides different answers to the questions above. (1) The Hobbesian or "realist" paradigm views international relations as a state of natm dominated by independent, self-reliant states struggling for power and prestige in a milieu inimical to cooperation and devoid of international norms or momlity. (2) The Grotian or "internationalist" tradition views intemational Elations as the arena of sovereign states, but acting in a milieu characterized by pervasive interdependence in economic, military, legal, and political concerns. The possibility of ethical considerations is stronger in this environment since a rudimentary international society of common values, interests, and institutions does exist. (3) The Kantian or ...